Tendência de Sífilis em Gestante e Congênita nos municípios da Região de Saúde Centro Sul, Goiás, 2007-2018 - Camargo Tobias, Gabriela; Carvalho de Aquino, Erika (Journal of Health Care, 2021)
Objective: to estimate trends in the detection of syphilis in pregnant and congenital women in the municipalities of the Centro Sul de Goiás Health Region. Methods: epidemiological study of time series with data on syphilis notifications from 2007 to 2018. Data obtained from the Diseases and Notifications System, available on the website of the Unified Health System Database (DATASUS). Results: 1,217 syphilis cases were identified in pregnant women and 362 cases of congenital syphilis. The detection rate of syphilis in pregnant women was increasing for Aparecida de Goiânia, Aragoiânia, Bela Vista de Goiás, Bonfinópolis, Cristinópolis, Edeia, Indiara, Jandaia, Leopoldo de Bulhões, Orizona, Senador Canedo, Vianópolis and Vicentinópolis. The detection rate of congenital syphilis was increasing for Aragoiânia, Bela Vista de Goiás, Bonfinópolis, Leopoldo de bulhões and Orizona. Conclusions: the incidence of syphilis suggests failures in health care and indicates the need for new strategies to reduce disease transmission.
Keywords: Congenital Syphilis. Pregnancy. Time Series Studies